Analisa Peluang Dan Ancaman Perdagangan Bebas Produk Pertanian Sektor Kelapa Sawit - Arya Sugarda; Eka Radita Putri; N. Lara Santi; Wina Yuliana; Daspar (CV. ITTC INDONESIA, 2024)
Free trade has become a major focus in the international economy, with a significant impact on the agricultural sector, including palm oil. This analysis aims to evaluate the opportunities and threats faced by the palm oil sector in the context of free trade. In this analysis, opportunities such as wider market access and increasing global demand for palm oil are taken into account. However, these opportunities can also be offset by threats such as increased competition from other producers, changes in environmental regulations, and pressure from sustainability advocacy groups. Indonesia and Malaysia have good relations in bilateral palm oil commodity relations. In creating this scientific work the author used demand theory, bilateral economic cooperation, and interdependence which are useful for analyzing the studies in it, and in this type of research writing used descriptive-quantitative to process existing data. The productivity of palm oil export and import activities, one of which dominates palm oil as the top export commodity. Through a comprehensive approach to these opportunities and threats, stakeholders in the palm oil sector can take strategic steps to strengthen their position in the global market, while also paying attention to their impact on environmental and social sustainability.